Synthesis and characterization of lithium fluoride-doped Mg/ Cr, Cu/ Ni nanoparticles - Abdulhusian, Ali Jassem (2017)
Tissue equivalent thermoluminescent dosimeters (TLDS) are an effective device to measure low and high absorbed doses of ionizing radiation in protected area, medical and industrial applications or as a personal monitoring dosimeter. A number of commercially available TLDS are common for this purpose where the TL intensity is proportional to absorbed dose but they are of a narrow dose range. In this study effort were made to enhance the present TL performance of these materials to a wider dose range by employment of nanosynthesis method and introducing impurities to the TL materials. In this research the TLDS are fabricated from lithium fluoride doped by Mg/Cr, Cu/Ni and phosphor. LiF:Mg,Cu,P and LiF:Cr,Ni,P nanocrystales were synthesized by thermal treatment method from aqueous solution including lithium chloride (LiCl), ammonium fluoride (NH4F), deionized water, with the doping magnesium nitrate (MgNO3), copper nitrate (CuNO3), chromium nitrate (CrNO3), nickel nitrate (NiNO3) and ammonium hydrogen phosphate ((NH4)H2PO4) and polyvinyl pyrrolidone as surfactant agent. The samples were annealed from 723 to 1023 K. The characterization of the prepared samples of LiF:Mg,Cu,P and LiF:Cr,Ni,,P were done by using X- ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), (UV-vis) and Thermo Gravimetric Analysis (TGA). In TGA, the solvent evaporation caused weight loss in synthesized nanoparticles which had initial weight of 53.46 °C, the weight loss was about 5.19%. The temperature for initial decomposition (Tonset) is between (250 °C and 500 °C). Nevertheless, the greatest weight loss of 86.67% occurs at temperature of 445.53°C (Tmax) as a result of loss of a part of the organic material likes CO2 and gases. The XRD patterns of synthesized LiF nanoparticles showed the peak positions at 2θ values of 38.797°, 45.104°, 65.691°, 78.988°and 83.254° matching with (111), (002), (022), (113) and (222) crystalline plans. The average crystallite size of all samples was calculated from the line broadening of the diffraction peaks and most intense using Scherer’s formula. The TEM images which show cubical lithium fluoride nanoparticles with uniform morphology and particle size distributions. The TEM results showed that the particle size increased with the calcination temperature increases from 1.29 nm at 723 K to 3.19 nm at 1023 K. The FT-IR analysis proves two principle of absorption band around 350 and 750 cm-1 which attributed to the Li-O and F-O respectively. The band gap energy was determined from UV-vis reflectance spectra were found to decrease with increase in calcination temperature from 4.28 eV at 723 K to 4.20 eV at 1023 K in LiF:Mg,Cu,P nanocrystals while in LiF:Cr,Ni,P nanocrystals the band gap decreased from 4.26 eV at 723 K to 4.22 eV at 1023 K due to particle size increased.